2014
DOI: 10.1007/s00484-014-0933-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cause-specific mortality during heat waves in central Spain, 1975–2008

Abstract: The relationship between heat waves and mortality has been widely described, but there are few studies using long daily data on specific-cause mortality. This study is undertaken in central Spain and analysing natural causes, circulatory and respiratory causes of mortality from 1975 to 2008. Time-series analysis was performed using ARIMA models, including data on specific-cause mortality and maximum and mean daily temperature and mean daily air pressure. The length of heat waves and their chronological number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 60 publications
(61 reference statements)
5
30
0
Order By: Relevance
“…On the one hand, in the first two decades the impact of cold on natural-cause mortality is similar to what has been observed for heat in this same region (Mirón et al 2014). As regards the pattern of specific-cause mortality, the impact of cold is less than that of heat for circulatory causes and greater for respiratory causes, a finding that is in line with the higher winter mortality linked to infectious respiratory-tract diseases and with the greater impact of cold on respiratory disease mortality (Ebi and Mills 2013).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…On the one hand, in the first two decades the impact of cold on natural-cause mortality is similar to what has been observed for heat in this same region (Mirón et al 2014). As regards the pattern of specific-cause mortality, the impact of cold is less than that of heat for circulatory causes and greater for respiratory causes, a finding that is in line with the higher winter mortality linked to infectious respiratory-tract diseases and with the greater impact of cold on respiratory disease mortality (Ebi and Mills 2013).…”
Section: Discussionsupporting
confidence: 76%
“…Studies conducted in this same geographical area have reported that heat-related mortality also decreased over the last 30 years (Mirón et al 2014), a trend which is in line with other studies undertaken elsewhere (Ha and Kim 2013;Schifano et al 2012) but is not as marked as occurs in the case of low temperatures.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Studies undertaken in CLM (Mirón et al 2014) and elsewhere around the world (Ha and Kim 2013) report a trend towards a decline in the impact of heat on mortality. It seems that socio-demographic and economic factors and health-service improvements might account for this effect (Mirón et al 2014). The influence of social factors is showing itself to be decisive in its relationship with other environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different parts of the world show that, far from remaining constant, these impacts are changing over time, with a trend towards the minimisation of such effects [19], i.e., while the effect is most pronounced in cardiovascular-cause mortality [20], it has remained practically constant in the case of respiratory-cause mortality [21]. These results, obtained from a time series covering a time span of over 30 years, show that the increase in risk of heat-related mortality for each degree centigrade that the threshold temperature is exceeded, went from 13.7% in the decade 1975-1985 to 7.4 % in the decade 1997-2008, and specifically, that this decline was due to circulatory causes, going from 18.2% in the period 1975-1985 to 5.8% in the period 1997-2008; in the case of respiratory causes, however, no such decline was in evidence, with the respective figures remaining practically constant, i.e., 11.8% in 1975-1985 versus 13.5% in 1997-2008.…”
mentioning
confidence: 99%